Optimal Assembly Position and Multi-objective Trajectory Optimization for Dual Robotic Arms Collaboration - Wang Tianrui; Tao Ping (Jixie chuandong)
In order to solve the limitation and randomness in determining the collaborative assembly position of dual robotic arms by the traditional manual demonstration method, and taking the coordinated assembly of dual robotic arms axle holes as the engineering background, this study uses the particle swarm algorithm to perform multiple searches for the optimal assembly position for the overall global flexibility in the collaborative assembly process and carries out multi-objective trajectory optimization based on the optimal position, with respect to the overall motion flexibility and trajectory planning of the robotic arm. Firstly, the motion constraint relationship in the coordinated assembly process of double robotic arms is analyzed, the operability degree is used as the flexibility evaluation index, the operability evaluation method of dual robotic arms collaborative assembly system is proposed, the optimization objective function is constructed, and the particle swarm algorithm is used to find the assembly position with the optimal global operability degree of the system in the collaborative space of double robotic arms. Finally, based on the optimal position of flexibility, the multi-objective particle swarm algorithm is used to optimize the trajectory with the objectives of time, energy consumption and impact; by performing simulation analysis in the Matlab robot simulation platform, the results show that, by applying the flexibility index to the trajectory planning, it can improve the operation efficiency of the robotic arm, while reducing energy consumption and impact loss, and maintain a high degree of operability during the whole motion process, effectively avoiding the randomness of the traditional manual teaching method, thus realizing the optimal flexible trajectory planning for collaborative assembly of dual robotic arms.